Histopathology reporting in large bowel cancer. Issue 5 (May 1981) - Blenkinsopp, W K; Stewart-Brown, S; Blesovsky, L; Kearney, G; Fielding, L P
Abstract : A review of histopathology reports on 2046 patients in the large bowel cancer project showed considerable observer variation in histological grading. Dukes staging, and lymph node harvest. These parameters have a well-established relationship to prognosis, but, if they are to be applied for both clinical and research purposes, they must be assessed consistently. A minimal level of information which should be recorded from a resection specimen is suggested, with a description of the methods by which this information can be obtained.